2020
DOI: 10.1038/s42003-020-0933-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the interaction between RNA-binding protein HuR and FOXQ1 suppresses breast cancer invasion and metastasis

Abstract: Patients diagnosed with metastatic breast cancer have a dismal 5-year survival rate of only 24%. The RNA-binding protein Hu antigen R (HuR) is upregulated in breast cancer, and elevated cytoplasmic HuR correlates with high-grade tumors and poor clinical outcome of breast cancer. HuR promotes tumorigenesis by regulating numerous proto-oncogenes, growth factors, and cytokines that support major tumor hallmarks including invasion and metastasis. Here, we report a HuR inhibitor KH-3, which potently suppresses brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 60 publications
2
70
0
Order By: Relevance
“…Treatment with KH-3 in vivo inhibited breast tumor growth comparing to that of vehicle control. Furthermore, the inhibitory capability of KH-3 on cancer cells was attenuated by HuR stable knockdown with the lentiviral shRNA, indicating the target selectivity of KH-3 [27]. Importantly, inhibition of HuR with KH-3 yielded a significant reduced in the progression of pathological cardiac hypertrophy in a transverse aortic constriction model, as evidenced by a reduction in hypertrophy, dilation and fibrosis, and preserved cardiac function [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with KH-3 in vivo inhibited breast tumor growth comparing to that of vehicle control. Furthermore, the inhibitory capability of KH-3 on cancer cells was attenuated by HuR stable knockdown with the lentiviral shRNA, indicating the target selectivity of KH-3 [27]. Importantly, inhibition of HuR with KH-3 yielded a significant reduced in the progression of pathological cardiac hypertrophy in a transverse aortic constriction model, as evidenced by a reduction in hypertrophy, dilation and fibrosis, and preserved cardiac function [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have discovered a series of small molecule HuR inhibitors at nM to sub-μM K i values, which dose-dependently inhibit the action of HuR by specifically disrupting HuR-ARE interaction [25,26]. The lead compound KH-3 exhibits superior potency in disrupting HuR-ARE interaction [27]. It has been shown that KH3 selectively inhibited the viability of cancer cells that had high levels of HuR but had no effect on normal cell line in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] Increasing numbers of studies have examined the role of FOXQ1 in tumor progression and it has been suggested that suppressing FOXQ1 expression may decrease invasion and migration in TNBC cell lines. 32,33 FOXQ1 has also been suggested as potentially being a driving force in the heterogeneity of BC. 6 Thus, additional knowledge of the role of FOXQ1 in BC could have the potential to improve the diagnosis and treatment of BC tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, through interaction with a variety of RNA binding proteins (RBPs), lncRNAs are known to participate in the regulation of RNA splicing and stability [ 64 ]. For instance, the RNA binding protein ELAVL1 (embryonic lethal abnormal vision-like protein 1), also known as HuR (Hu antigen R), is crucial for the nuclear import and stabilization of numerous RNA transcripts [ 65 ]. In OSCC, the oncogenic lncRNA SNHG3 (small nucleolar RNA host gene 3) was reported to be localized in the cytoplasm and capable of recruiting ELAVL1, and thereby stabilizing NFYC (transcription factor Y subunit gamma) mRNA to upregulate the expression of NFYC, which in turn promotes cell proliferation and migration [ 66 ] ( Figure 1 e).…”
Section: Mechanism Of Oral Cancer-associated Lncrnas In Tumorigenesismentioning
confidence: 99%